Skull base reconstruction with pedicled nasoseptal flap: Technique, indications, and limitations. Issue 1 (January 2019) - Reuter, Gilles; Bouchain, Olivier; Demanez, Laurent; Scholtes, Félix; Martin, Didier
Abstract: Endoscopic skull base surgery allows extensive tumor resection but results in large defects requiring robust dural repair. The vascularized nasal septal flap pedicled on the posterior nasal septal artery is known to have an excellent success rate for dural defect coverage. Detailed step-by-step descriptions of the harvest and placement of this flap are scarce. Using a sketch, images, and a video, we describe a detailed method for endoscopically harvesting and placing a nasoseptal flap (NSF). We also describe the indications and the decision process leading to the use of NSF.